2006
DOI: 10.1097/01.aog.0000214671.19023.68
|View full text |Cite
|
Sign up to set email alerts
|

Vasospasm of the Nipple Presenting as Painful Lactation

Abstract: Vasospasm of the nipple causes severe episodic breast pain and may lead to discontinuation of breastfeeding if not appropriately treated. This phenomenon is not well reported in the obstetric and gynecologic literature, although the obstetrician may be the first physician to evaluate a patient with symptoms. Patients with episodic nipple pain and pallor can be successfully treated with nifedipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Additionally, the many parallels between the infectious mastitis and ductal infection bodies of literature also may explain some of the unique traits of ductal infections. Thus, until randomized controlled trials of treatment are run or until there is information that conflicts with the hypotheses of biofilms and small‐colony variants, ruling out conditions like nipple vasospasm, 35 culturing women with these symptoms, and then treating them is a reasonable method of management. Empirical treatment using antibiotics or fluconazole or both can be based on maternal history and presentation, together with infant findings, or providers can wait to base treatment on culture results.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the many parallels between the infectious mastitis and ductal infection bodies of literature also may explain some of the unique traits of ductal infections. Thus, until randomized controlled trials of treatment are run or until there is information that conflicts with the hypotheses of biofilms and small‐colony variants, ruling out conditions like nipple vasospasm, 35 culturing women with these symptoms, and then treating them is a reasonable method of management. Empirical treatment using antibiotics or fluconazole or both can be based on maternal history and presentation, together with infant findings, or providers can wait to base treatment on culture results.…”
Section: Resultsmentioning
confidence: 99%
“…Examples are algodystrophy or acute posttraumatic ischaemic of the limbs [93], exercise-induced amaurosis fugax-like symptoms [94] due to vasospasm of the retinal arteries, painful and ischaemic mammilla provoked by nursing [95,96] or orgasmic headache due to transient vasospasm [97-99]. All these symptoms fortunately occur infrequently.…”
Section: General Symptoms and Signs Of Pvdmentioning
confidence: 99%
“…After delivery of the infant and prior to diagnosis of retained placenta, active management is recommended to facilitate spontaneous placental separation, including oxytocin, controlled cord traction, and uterine massage 4. These maneuvers have been shown to decrease the risk of postpartum hemorrhage, though it has not been shown that active management will prevent retained placenta 22…”
Section: Managementmentioning
confidence: 99%
“…This is typically diagnosed when the placenta fails to spontaneously separate during the third stage of labor when a patient experiences excessive bleeding in absence of placenta separation or if there is confirmation of placenta tissue remaining after the majority of the placenta delivers spontaneously 13. Placentas that fail to spontaneously separate can be a cause of significant surgical and hemorrhagic morbidity 4,5. Untreated, retained placenta is considered the second leading cause of postpartum hemorrhage (PPH) 5,6…”
Section: Introductionmentioning
confidence: 99%